ISLAMIC SYMBOL ON FASHION STYLE USED BY THE STUDENTS OF ADAB AND HUMANITIES FACULTY, UIN SUNAN AMPEL SURABAYA: SEMIOTICS STUDIES - Abdur Rohman (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
Abstract Fashion is not only has function to cover the body, but also it has relation to religion value. This research aims to describe islamic value toward the style of students fashion at Adab and Humanity Faculty, UIN Sunan Ampel Surabaya throught semiotics study. The theory that used in this research is Ferdinand De Saussure’s structuralism. It analyzes on sintagmatics, paradigmatic relation and context as the background. Descriptive qualitative is used in this research by semiotics concept. The data were taken from the picture of the students fashion and the quitioner that is filled by the students. The result of this research is 60% students fashion based on islamic value. While 40% of them did not wear Islamic fashion style. It is because the students have limited understanding of Islamic fashion rule. Keywords: Islamic Symbol, Fashion Style, Semiotics